Pengaruh Pengawasan, Pendelegasian Wewenang dan Komunikasi Terhadap Prestasi Kerja Pegawai Puskesmas Pada Dinas Kesehatan Pengendalian Penduduk dan Keluarga Berencana Kabupaten Lingga - Afdillah, Yasir; Rifanto, Royhandy; Kartini, Umar Wira; Sabri, Sabri; Suyono, Suyono (Asosiasi Ide Bahasa Kepri, 2024)
This study was conducted with the aim of determining the effect of supervision, delegation of authority and communication on the work performance of Puskesmas employees at the Lingga Regency Population Control and Family Planning Health Office. The population in this study was 462 employees. The determination of the number of samples using the slovin formula with an error rate of 10%. So that the number of samples was obtained as many as 82 respondents. The sampling technique is by probability sampling. Data collection was carried out by distributing questionnaires to respondents. The collected data is processed using SPSS data processing software. From the results of the study, it is known that partially, supervision has a significant effect on employee work performance, delegation of authority has a significant effect on employee work performance and communication has a non- significant effect on employee work performance. Simultaneously, it is known that supervision, delegation of authority and communication have a significant effect on employee performance. The adjusted R square value is 0.744 or 74.4%, which means that supervision, delegation of authority and communication can affect employee performance by 74.4%. While the remaining 25.6% was influenced by other factors not described in this research model